2014
DOI: 10.1371/journal.pone.0104477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Tranexamic Acid on Bleeding and Quality of Surgical Field during Functional Endoscopic Sinus Surgery in Patients with Chronic Rhinosinusitis: A Triple Blind Randomized Clinical Trial

Abstract: BackgroundThe effect of tranexamic acid (TXA) on bleeding and improvement of surgical field during functional endoscopic sinus surgery (FESS) is not clear yet. This study was conducted to answer this question.MethodsThis trial was conducted on 60 patients with chronic sinusitis at Beasat Hospital, Hamadan, Iran, from April to November 2013. Thirty patients in the intervention group received three pledgets soaked with TXA 5% and phenylephrine 0.5% for 10 minutes in each nasal cavity before surgery. Thirty patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 24 publications
3
50
0
2
Order By: Relevance
“…Intraoperative hemorrhage control is one of the most important factors for improving the surgical field to ensure a successful operation. Due to the narrow operative field of the nasal cavity, even slight bleeding can distort the view of the endoscope and increase the occurrence of important structure injuries, cause the surgery to take longer, or even result in inconclusive surgery . The previous meta‐analysis demonstrated that topical or systemic tranexamic acid decreases intraoperative bleeding and enhances surgical field quality, similar to our results.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Intraoperative hemorrhage control is one of the most important factors for improving the surgical field to ensure a successful operation. Due to the narrow operative field of the nasal cavity, even slight bleeding can distort the view of the endoscope and increase the occurrence of important structure injuries, cause the surgery to take longer, or even result in inconclusive surgery . The previous meta‐analysis demonstrated that topical or systemic tranexamic acid decreases intraoperative bleeding and enhances surgical field quality, similar to our results.…”
Section: Discussionsupporting
confidence: 88%
“…Due to the narrow operative field of the nasal cavity, even slight bleeding can distort the view of the endoscope and increase the occurrence of important structure injuries, cause the surgery to take longer, or even result in inconclusive surgery. 27 The previous metaanalysis demonstrated that topical or systemic tranexamic acid decreases intraoperative bleeding and enhances surgical field quality, 24 similar to our results. Reasonably, improvement in the quality of the surgical field correlated with the surgeon's satisfaction.…”
Section: Discussionsupporting
confidence: 87%
“…The efficacy of topical application of the injectable form of tranexamic acid (TXA) has been shown beneficial for the treatment of idiopathic anterior epistaxis . Additionally, topical use of TXA during oral, pulmonary, sinus, and adenoidectomy procedures results in significantly less mucosal bleeding. In this study, we compared the effect of topical TXA with ANP for treatment of anterior epistaxis in patients taking antiplatelet drugs.…”
mentioning
confidence: 99%
“…Extrapolating from other clinical applications, two RCTs showed that topical TXA in FESS significantly improved visual field and reduced blood loss; however, the trials were small and one had a high risk of bias. A large ( n = 400) well‐designed trial found that topical TXA applied post‐adenoidectomy in children reduced blood loss and primary haemorrhage rate.…”
Section: Discussionmentioning
confidence: 99%